IMMISCIBILITY OF CALCIUM FLUORIDE AND ALUMINOSILICATE MELTS IN ONGONITE FROM THE ARY-BULAK INTRUSION, EASTERN TRANSBAIKAL REGION - Peretyazhko I.S.; Zagorsky V.Y.; Tsareva E.A.; Sapozhnikov A.N. (My University, 2007)
The addition of fluorides of Na, K, Ca, and other elements into silicate melts lowers the degree of their homogeneity owing to the formation of sybotaxic groups enriched in fluorine and cations-modifiers. Many fluoride–silicate systems are characterized by a microheteregoneous structure in the hyperliquidus region related to immiscibility. Under certain conditions, the evolution of natural magmatic systems gives rise to the formation of fluoride melts. Such examples are not numerous and mostly pertain to the effects of immiscibility in sodic fluoride melts (melts–brines) associated with peralkaline granitic magmas. The existence of calcium fluoride melts is confirmed by inclusions of fluoritic glass in mantle xenoliths captured by alkali basalt in New Zealand.